Dietitians' practice in giving carbohydrate advice in the management of type 2 diabetes: a mixed methods study - McArdle, Paul D.; Greenfield, Sheila M.; Avery, Amanda; Adams, Gary G.; Gill, Paramijt S. (Wiley, 2016)
Background: Carbohydrate is accepted as the principal nutrient affecting blood glucose in diabetes; however, current guidelines are unable to specify the optimal quantity of carbohydrate for glycaemic control. No studies exist that describe current practice amongst healthcare professionals giving carbohydrate advice in type 2 diabetes. The present study aims to improve understanding of the degree of variation in the current practice of UK registered dietitians (RDs) by describing how RDs advise patients. Methods: UK RDs were contacted through national networks and asked to complete an online survey, which was analysed using stata, version 12 (StataCorp, College Station, TX, USA). Three consultations between dietitians and patients with type 2 diabetes were observed, followed by semi-structured interviews with the dietitians. Results: In total, 320 complete survey responses were received. Dietitians' advice varied according to expertise, training and confidence, and the complexity of the patient's blood glucose treatment. Some 48% (n = 154) of respondents advised patients to restrict carbohydrate intake either occasionally or frequently, with 35.6% (n = 114) considering 30–39% of total energy from carbohydrate to be a realistic expectation. The overall theme from the interviews was ‘Conflicting Priorities’, with three sub-themes: (i) how treatment decisions are made; (ii) the difference between empowerment and advice; and (iii) contradictory advice. A disparity existed between what was observed and interview data on how dietitians rationalise the type of carbohydrate advice provided. Conclusions: Dietitians' advice varies for a number of reasons. Consensus exists in some areas (e.g. carbohydrate awareness advice); however, clear definitions of such terms are lacking. Clarification of interventions may improve the consistency of approach and improve patient outcomes.